KEANEKARAGAMAN VEGETASI PADA HUTAN ADAT BUKIT TUNGGAL DI DESA BATU NANTA KECAMATAN BELIMBING KABUPATEN MELAWI - Putra, Adi; Budhi, Setia; Darwati, Herlina (JURNAL HUTAN LESTARI, 2017)
The existence of indigenous forest is very important as it constitutes a source of the see-producing area and can be also user as a research site. Unfortunately, the information about types of vegetation in the area of Bukit Tunggal forests is relatively scarce. This research aims to describe the vegetation diversity in Bukit Tunggal forests and to identify types of vegetation which are the most dominant in the area. This research was conducted for 4 week in the indigenous forest of Bukit Tunggal at Batu Nanta Village, Belimbing sub-district, Melawi. A survey method was employed in this research through a vegetation analysis with a line of terrace. The research was carried out by creating 3 lanes with the length and distance of each lanes varied depending on the condition of the field. Results of the discussion showed that there were 77 types of vegetation which could be grouped into 37 families ranging from a seedling stage (including lower plants, shrubs, bushes, and lianas), stapling, poles, to trunks. The vegetation diversity in Bukit Tunggal forests indicated that the area had a high diversity with a good conservation value. In addition, the forests has various germplasms. Results of a quantitative analysis of crucial value index (INP) at every growth level in general was dominated by meranti (Shorea spp.) of Dipterocarpaceae family. There needs, therefore, efforts to preserve the existence of this area in addition to the current conservation which has been planned and executed well, for example by enriching types and rehabilitation.Keywords: Indigenous forests of Bukit Tunggal, diversity, crucial value index, and type domination.